L’abbaye de Montebourg en Angleterre (XIe-XIIIe siècle) - Christophe Mauduit (Tabularia)
During the writing of Domesday Book, the abbey of Montebourg is the only monastery of the bishopric of Coutances to be endowed in England. Some years later, the abbey thinks it is entrusted to Richard de Reviers (d. 1107), faithful man of Henry I, who endows it widely across the Channel (Isle of Wight, Devon, Dorset, Berkshire). Montebourg is found then at the head of a large temporal, which does not fail to be disputed every so often. In the thirteenth century, the abbot of Montebourg becomes canon of Salisbury, underlining so more strongly the narrow relations of Montebourg with the English ecclesiastical world.